Implementasi model pembelajaran discovery learning untuk meningkatkan kemampuan pemecahan masalah serta habits of mind siswa SMP kelas VII - Hopipah, Ai; Rohaeti, Euis Eti; Nurjaman, Adi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
This study aims to determine the effect of the discovery learning model in improving mathematical problem solving abilities and habit of minds of class VII middle school students. The research method used in this study is quasi experiment. This research was carried out in one of the private junior high school in the city of Cimahi by selecting two classses, namely VII A dan VII B. Each clas has 30 students. The instruments used were 5 questions on problem solving ability and habit of mind. Data in the form of test result and questionnaries were processed using the N-gain test and the difference test between two averages with the help of the SPSS. The result showed that the class whose learning used the discovey learning model had mathematical problem solving ablities and students’ habit of minds better than the class which used ordinary learning.